1997
DOI: 10.1089/thy.1997.7.633
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Transforming Growth Factor β1 Messenger Ribonucleic Acid Expression in Porcine Thyroid FolliclesIn vitroby Growth Factors, Iodine, or δ-Iodolactone

Abstract: Transforming growth factor beta 1 (TGF beta 1) is an autocrine growth factor for thyrocytes and is supposed to be the mediator of iodine-induced growth inhibition of thyroid epithelial cells, but this is still controversial. We further investigated this hypothesis using intact porcine thyroid follicles ex vivo in a three-dimensional culture system. In this culture system it has been shown previously that both iodide as well as delta-iodolactone, the putative iodocompound mediating thyroid cell proliferation, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
24
0
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 21 publications
7
24
0
2
Order By: Relevance
“…This assumption is supported by findings of Ga¨rtner et al (1997), who could show a decreased expression of TGF-b1 mRNA after TSH stimulation of thyrocytes. Moreover, TGF-b1 has been shown to inhibit iodine uptake, iodine organification and thyroglobulin expression (Pang et al, 1992;Taton et al, 1993), as well as cell proliferation in different thyroid cell culture systems (Tsushima et al, 1988;Colletta et al, 1989;GrubeckLoebenstein et al, 1989;Depoortere et al, 2000).…”
Section: Genmapp Analysissupporting
confidence: 63%
“…This assumption is supported by findings of Ga¨rtner et al (1997), who could show a decreased expression of TGF-b1 mRNA after TSH stimulation of thyrocytes. Moreover, TGF-b1 has been shown to inhibit iodine uptake, iodine organification and thyroglobulin expression (Pang et al, 1992;Taton et al, 1993), as well as cell proliferation in different thyroid cell culture systems (Tsushima et al, 1988;Colletta et al, 1989;GrubeckLoebenstein et al, 1989;Depoortere et al, 2000).…”
Section: Genmapp Analysissupporting
confidence: 63%
“…Co-localization of furin and its substrate TGFb was also observed in regenerating liver hepatocytes (Hoshino et al, 1997) and in laminar flow-loaded vascular endothelial cells (Negishi et al, 2001), and furin was shown to convert the TGFb precursor to its active form in the present study. These two proteins may be controlled by stimulants in a coordinated manner, and indeed, TGFb production was reportedly increased by EGF-R stimulation in enterocytes (Dignass and Podolsky, 1993) and thyrocytes (Gartner et al, 1997). Chief cells express a high level of EGF-R as reported previously , and EGF-R stimulation by TGFa increased the expression of furin and TGFb and promoted the production of a processed form of TGFb.…”
Section: Discussionsupporting
confidence: 64%
“…Mehrere Arbeitsgruppen zeigten in den vergangenen Jahren, dass das Wachstum benigner Knoten vom intrathyreoidalen Jodangebot abhängt und zusätzlich lokale Wachstumsfaktoren wie EGF, IGF-1 u. a einen Einfluss ausüben [7,8,11,13,38,39,40]. Das Belassen dieser wachstumsstimulierbaren Knoten im Schilddrüsenrestparenchym kann im weiteren Verlauf unabhängig von der TSH-Stimulation oder dem intrathyreoidalen Jodangebot zur Entwicklung einer Rezidivstruma führen.…”
Section: Struma Benigna · Totale Thyreoidektomie · Chirurgie · Kompliunclassified